A case of multiple solitary neurofibromas located in the hypopharynx and cervical esophagus - Hamada Kazu; Shimode Yuzo; Hata Yoshiyuki; Kunou Hiroaki; Kobayashi Rika; Matsunaga Kazuhiro; Kawaura Ken; Mukai Tsuyoshi; Kitakata Hidekazu; Itoh Tohru; Okuro Masashi; Yamada Sohsuke (DEN Open)
Abstract A 50‐year‐old female was admitted to our hospital because of mild throat discomfort. Esophagogastroduodenoscopy demonstrated multiple 2–3 mm diameter whitish granules in her hypopharynx and cervical esophagus. Based on biopsy specimens, we considered the lesions to represent normal tissue or very mild mucosal dysplasia. However, S‐100 immunohistochemical staining 3 years later led to a diagnosis of multiple solitary neurofibromas located in the hypopharynx and cervical esophagus. Histological finding characteristics of neurofibroma were present in 72.7% of hypopharyngeal biopsy specimens and 33.3% of esophageal specimens. When diagnosing neurofibroma, it is important to perform biopsies at multiple locations and at different times and to enlist the cooperation of endoscopists and pathologists for immunohistochemical staining with S‐100.